The Process of Sharing Photography Knowledge in the PKK Program Government Assistance Class with Edupro - Shifa Salsabilla (Bina Nusantara University, 2025)
Abstract: This research aims to examine the photography class learning process implemented by GSNP EDUPRO (Galeri Nila Photoworks Education Program) through a government assistance program. The study was conducted using a field research approach with qualitative research methods. Data collection was performed through direct observation and documentation of learning activities. The research findings indicate that the process of sharing photography knowledge at GSNP EDUPRO is implemented through a structured mentoring method by photography experts who possess competency certificates in their field. The curriculum encompasses both theoretical and practical aspects of photography, ranging from photography history, compositional fundamentals, exposure triangle, lighting techniques, photography occupational health and safety, digital image processing, to unique selling propositions. The learning process is conducted directly through field practice in various locations with diverse lighting conditions and subjects. Mentors provide intensive guidance throughout the learning process using personalized approaches tailored to the needs and comprehension levels of individual participants. Progress evaluations are conducted periodically to ensure the achievement of expected competency standards. The learning program concludes with a standardized photography competency examination through collaboration with the Photography Competency Certification Board of Indonesia (LESKOFI), providing added value in the form of official certification for participants who successfully complete the program. This research concludes that the photography education implemented by GSNP EDUPRO through the government assistance program has effectively transferred photography knowledge and skills, with success measured by participants' passing rates in the LESKOFI competency certification examination.